PENERAPAN METODE MNEMONIC BERBANTUAN MEDIA GAMBAR UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN IPA KELAS IV SDN 42 MATARAM TAHUN 2017/2018 - Baiq Winda Rahmatia; Ahmad Harjono; Heri hadi Saputra (Indonesian Publication Center, 2020)
This study aims to improve students learning outcomes by applying the images media assisted mnemonic method. This research is a Classroom Action Research conducted in two cycles. The data were collected by using objective test in consisting of 10 multiple choice items, and the data of teacher and student activity were taken through observation sheet. Observation sheets are used to find out the level of teacher and student activity assisted mnemonic method in the learning process by applying image media during the learning took place. Student learning outcomes in the first cycle reached an average of 75.5 with a percentage of 70% classical completeness and increased in cycle II to 84.28 with the percentage of classical completeness 85.71%. This it can be concluded that application of image media assisted mnemonic method can improve student learning outcomes in science subjects of class IV B SDN 42 Mataram.